Therapeutic value of stimulating the nitrate‐nitrite‐nitric oxide pathway to attenuate oxidative stress and restore nitric oxide bioavailability in cardiorenal disease - Carlstrom, M.; Montenegro, M. F. (Journal of internal medicine, 2019)
Cardiovascular disorders including hypertension and associated renal disease are major health problems affecting more than 1.5 billion people worldwide. Apart from nonmodifiable factors such as ageing, family history and gender, both sedentary lifestyle and unhealthy dietary habits are considered as major risk factors. The disorders are interrelated suggesting common pathological pathways. Mechanistically, oxidative stress and compromised function of the nitric oxide synthase (NOS) system leading to endothelial dysfunction and reduction in nitric oxide (NO) bioavailability have been widely implicated and associated with development and progression of disease. New strategies that correct this redox imbalance and increase NO bioactivity may have major clinical implications. The inorganic anions, nitrate and nitrite, are endogenously formed by oxidization of NOS‐derived NO, but there are also high amounts of nitrate in our daily diet. In this regard, accumulated evidence over the past two decades demonstrates that these anions can be recycled back to NO and other bioactive nitrogen oxides, thus offering an attractive alternative strategy for therapeutic exploitation. In this review, we describe how dietary stimulation of the nitrate–nitrite–NO pathway affects cardiovascular and renal functions in health and disease via modulation of oxidative stress and NO bioavailability. Clinical studies addressing potential effects on the renal system are still limited, but blood pressure‐lowering effects of nitrate supplementation have been demonstrated in healthy and hypertensive subjects as well as in patients with chronic kidney disease. However, larger clinical studies are warranted to reveal whether chronic nitrate treatment can slow‐down the progression of cardiorenal disease and associated complications.